Optimizing ultrashort laser pulse compression by two photon absorption. (23rd February 2016) - Welch, G.; Frisch, J.; Smith, S.; Glownia, J.M.; Fry, A.
Abstract: Demonstrated is an approach for relative optimization of ultrashort pulses using two-photon generated photocurrent in a GaAsP photodiode. Two-photon absorption is a nonlinear process, allowing for highly sensitive tuning of ultrashort laser systems.